Effect of preharvest ethephon application on selected biochemical components and polyphenol oxidase activity in macadamia nuts - Aruwajoye, Noluthando Noxolo; Mditshwa, Asanda; Magwaza, Lembe Samukelo; Ngidi, Mjabuliseni Simon C.; Tesfay, Samson Zeray (MDPI, 2023)
Ethephon is a plant growth regulator that triggers diverse responses in plants, such as fruit ripening, leaf senescence, hull senescence, stem elongation, and nut abscission. This study examined how the preharvest application of ethephon 480 SL® affects selected biochemical components and polyphenol oxidase (PPO) activity in two macadamia nut cultivars: ‘788’ and ‘Beaumont’. Ethephon was applied to the trees via a Cima mist blower at rates of 13.33 mL/L per hectare for the ‘788’ cultivar and 16.67 mL/L per hectare for the ‘Beaumont’. Following harvest, the nuts were stored at 25 °C for 72 days, and samples were taken at 18-day intervals. Standard procedures were used to assess the following: total phenolics, total flavonoids, 2,2,-diphenyl-1-picrylhydrazyl (DPPH) assay, Ferric reducing ability power (FRAP) assay, sucrose, total protein, and PPO activities. This evaluation was carried out across a total of four treatments: ethephon-treated nuts from the orchard floor (ED), ethephon-treated nuts from the tree (ET), untreated nuts from the orchard floor (CD), and untreated nuts from the tree (CT). The evaluation’s outcomes were analyzed using a principal component analysis (PCA), a correlation matrix heat map (CMHM), and a graphical assessment. The results unveiled significant correlations and associations among the assessed parameters. The correlation matrix heat map analysis highlighted a strong positive correlation (0.97) between the sucrose and the PPO activity in the ‘Beaumont’ cultivar, supported by the PCA analysis identifying the ED treatment as the most influential. At the storage period’s conclusion, the ED treatment had the highest sucrose content (18.63 mg/g) and polyphenol oxidase activity (1.06 U g−1). In the ‘788’ cultivar, a close relationship emerged between the phenolic content, the PPO activity, and the Ferric reducing antioxidant power (FRAP)’s antioxidant activity. Consistently, the CT treatment (untreated nuts) demonstrated positive correlations with several key parameters in both cultivars, displaying heightened phenolic content and antioxidant activities. Consequently, our findings indicate that the CT treatment, involving tree-harvested nuts without ethephon application, could be the preferred option for sustaining macadamia nuts’ quality and shelf life compared to other methods. Moreover, our study underscores the significance of proper storage conditions for maintaining the desired biochemical parameters of macadamia nuts. By comprehending the effects of distinct treatments and harvesting techniques, producers and processors can devise strategies to optimize storage conditions and uphold macadamia nut quality.
Keywords: ethephon; preharvest; abscission; macadamia nuts; postharvest; quality; nutrition